2020
DOI: 10.1192/j.eurpsy.2019.11
|View full text |Cite
|
Sign up to set email alerts
|

Toward operationalizing deficient emotional self-regulation in newly referred adults with ADHD: A receiver operator characteristic curve analysis

Abstract: Background. A growing body of research suggests that deficient emotional self-regulation (DESR) is common and morbid among attention-deficit/hyperactivity disorder (ADHD) patients. The main aim of the present study was to assess whether high and low levels of DESR in adult ADHD patients can be operationalized and whether they are clinically useful. Methods. A total of 441 newly referred 18- to 55-year-old adults of both sexes with Diagnostic and Statistical Manual of Mental Disorders: Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 17 publications
8
23
0
Order By: Relevance
“…In contrast to the measurement of functional impairment, which measures individual performance parameters in a speci c task or context, such as work or driving performance, QoL assessment allows for a wider perspective on productivity, relationships and well-being. However, only two studies to date reported signi cant associations between QoL in ADHD and a subset of ED constructs, namely emotional impulsivity and de cient emotional self-regulation (42,45). The current study adds an additional component by showing the unique contribution of multiple ED aspects to QoL, beyond the contribution of ADHD symptoms.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In contrast to the measurement of functional impairment, which measures individual performance parameters in a speci c task or context, such as work or driving performance, QoL assessment allows for a wider perspective on productivity, relationships and well-being. However, only two studies to date reported signi cant associations between QoL in ADHD and a subset of ED constructs, namely emotional impulsivity and de cient emotional self-regulation (42,45). The current study adds an additional component by showing the unique contribution of multiple ED aspects to QoL, beyond the contribution of ADHD symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, only a handful of studies have examined the direct contribution of ED to QoL in ADHD, yielding mixed results. Using a clinical sample of adults with ADHD, two studies reported that ED severity was signi cantly associated with ADHD symptoms severity and with QoL, regardless of medication status (42,45). On the other hand, in a study which examined the neuropsychological factors in a general population of young adults, ED was not found to be a unique contributor to QoL beyond other neuropsychological de cits (46).…”
Section: Introductionmentioning
confidence: 97%
“…Children with ADHD reported an impairment in measures of alertness compared to children with typical development, which appears to be due to low levels of arousal ( 31 ); moreover, they showed an impairment in measures of selective and divided attention and an increased variability in reaction times in sustained attention tasks compared to their healthy peers ( 32 ). The reaction time and its variability, considered a measure of attention ( 33 ), may be affected by symptoms commonly observed in children with ADHD, including distractibility, deficient self-regulation of motivation and/or impaired perseverance ( 34 , 35 ). Evidence of increased variability in reaction time in ADHD led to the formulation of a mechanistic hypothesis of default network interference.…”
Section: Attentional Dysfunction and Methylphenidatementioning
confidence: 99%
“…ADHD is often accompanied by affective and behavioral problems [ 19 ] that are not included in the ADHD criteria listed in the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition (DSM-5) [ 20 ]. Multiple studies have evidenced that people with ADHD have more comorbid internalizing (e.g., depressive, anxious, and somatic symptoms) and externalizing symptoms (e.g., oppositional defiance and conduct problems) than do people without ADHD [ 21 , 22 , 23 , 24 , 25 , 26 ]. Comorbid internalizing and externalizing symptoms not only worsen functional outcomes during childhood [ 27 ] but also predict ADHD persistence from childhood into adulthood and adverse outcomes in adulthood among children with ADHD [ 28 ].…”
Section: Introductionmentioning
confidence: 99%